2021
DOI: 10.1093/jscr/rjab198
|View full text |Cite|
|
Sign up to set email alerts
|

Acute abdomen in a 54-year-old COVID-19 patient: a case report

Abstract: Although primarily a respiratory virus, coronavirus-19 acts on the gastrointestinal tract to cause symptoms such as anorexia, nausea, vomiting and diarrhea. One possible mechanism involves the ACE2 receptor, which serves as the primary receptor for virus entry into the gastrointestinal epithelium. We describe the case of a 54-year-old-male with recent coronavirus disease 2019 (COVID-19) infection, who later presented with nausea, vomiting, diarrhea and progressively worsening diffuse abdominal pain for 1 week.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…One of the suggested mechanisms for paralytic ileus/small bowel obstruction is through the inflammatory process from the virus entry into the small intestine and leading to micro thrombosis of the microcirculation 32 . Studies have shown that in patients infected with coronavirus gastrointestinal involvement is seen in at least two‐thirds of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the suggested mechanisms for paralytic ileus/small bowel obstruction is through the inflammatory process from the virus entry into the small intestine and leading to micro thrombosis of the microcirculation 32 . Studies have shown that in patients infected with coronavirus gastrointestinal involvement is seen in at least two‐thirds of patients.…”
Section: Discussionmentioning
confidence: 99%
“…30 One of the suggested mechanisms for paralytic ileus/small bowel obstruction is through the inflammatory process from the virus entry into the small intestine and leading to micro thrombosis of the microcirculation. 32 Studies have shown that in patients infected with coronavirus gastrointestinal involvement is seen in at least twothirds of patients. Coagulation abnormalities and elevated D-dimer levels were noted in patients with COVID-19 and are related to a poor clinical outcome and a very high inpatient mortality rate.…”
Section: Diagnosis Sequela and Prognosismentioning
confidence: 99%
“…[1] Gastrointestinal (GI) manifestations are common extrapulmonary presentations of COVID-19, as the GI tract is involved in the early stages of the disease and is an important entry site for the viruses. [2][3][4] GI manifestations, which include abdominal pain, anorexia, nausea, vomiting, and diarrhea, may appear even earlier than respiratory symptoms. [4,5] Common entities include enterocolitis, ileus, and bowel ischemia due to thromboembolisms associated with coagulopathy.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 , 4 ] In addition, intestinal obstruction without a predisposing cause is rarely reported in patients with COVID-19. [ 3 , 6 ] Previous research has proposed that the angiotensin-converting enzyme 2 receptor mediates viral entry to the GI tract and microthrombosis formation. [ 4 ] Several potential theories regarding GI presentation during COVID-19 such as fecal to oral transmission or concept of the microbiota alteration have been reported.…”
Section: Introductionmentioning
confidence: 99%